2016
DOI: 10.1177/1687814016674097
|View full text |Cite
|
Sign up to set email alerts
|

Iterative tuning notch filter for suppressing resonance in ultra-precision motion control

Abstract: In this article, a practical iterative algorithm for tuning the parameters of notch filter is presented to suppress highfrequency resonance in ultra-precision motion control. Notch filter is a useful tool to suppress middle-and highfrequency resonance to improve control precision. The traditional tuning method for it depends on the Fourier transform of the positioning error or the modal analysis of the motion stage, which cannot get the optimal control performance. The proposed algorithm can be used to tune th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In order to eliminate disturbance and maintain the small CD, many different kinds of algorithms have been presented, such as the laser direct writing method 1 . An ultra‐precision motion control algorithm has been developed to obtain the high positioning precision of the step‐and‐scan projection photolithography 2 . To meet the requirement for precise overlay, a multifield sub‐5 nm overlay algorithm has been proposed in imprint lithography 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to eliminate disturbance and maintain the small CD, many different kinds of algorithms have been presented, such as the laser direct writing method 1 . An ultra‐precision motion control algorithm has been developed to obtain the high positioning precision of the step‐and‐scan projection photolithography 2 . To meet the requirement for precise overlay, a multifield sub‐5 nm overlay algorithm has been proposed in imprint lithography 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the iteratively tuning method has the advantage that it can guarantee both the performance and robustness in theory. It is found that this method has succeeded in tuning the parameters of many types of controllers, such as notch filters, 27 feedback controllers, 28 and admittance controllers. 29 When it is used to tune the model-based feed-forward controller, it can make the tracking error converge to zero for various trajectories because the controller has good extrapolation capabilities to the commands.…”
Section: Introductionmentioning
confidence: 99%